Application of BS4-enzyme on the methane production from mixture of cattle manures and waste paper - Tuti Haryati; A. P. Sinurat; B. Listian; H. Hamid; T. Purwadaria (Indonesian Center for Animal Research and Development (ICARD), 2016)
Cellulose from abundant newspaper waste could be transformed into methane through anaerobic fermentation. This research was carried out to compare the gas production including methane between samples containing feces and waste paper mixture as inoculum and substrate, respectively and added with and without BS4 enzyme. The enzyme was produced in Indonesian Research Institute of Animal Produce (IRIAP) by growing Eupenicillium javanicum BS4 in coconut meals. There were three treatments, i.e., 30% manure (M30); 15 % manure + 15 % paper waste (MP 30); MP30 + 3 mL BS4 enzyme equal to 0.42 U/g dry matter (MPE30) The percentage of waste papers addition in feces was calculated on dry matter (DM) basis and every treatment had five replications. Total gas and methane productions were measured weekly, while dry matter losses were determined during 5 week fermentation. Interactions between treatments and incubation time were analyzed using completely randomized design each week. Kind of substrates influenced both total gas and methane productions during incubation time. Both waste papers and enzyme addition enhanced gas production. The highest total gas and methane productions for five weeks incubation were highly significantly observed (P<0.01) in MP30 and MPE30 compared to M30. Addition of enzyme significantly increased total gas and methane productions in the first week. The highest methane and total gas yield/g dry matter were obtained by BS4 enzyme addition. It was concluded that BS4 enzyme is good in accelerating and increasing the transformation efficiency of waste paper and manure mixture for biogas production.